O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation is a rare event in soft tissue sarcoma - Jakob, Jens; Hille, Maren; Sauer, Christian; Ströbel, Philipp; Wenz, Frederik; Hohenberger, Peter (Radiation oncology, 2012)
Gene silencing of O6-methylguanine-DNA methyltransferase (MGMT) by promoter methylation improves the outcome of glioblastoma patients after combined therapy of alkylating chemotherapeutic agents and radiation. The purpose of this study was to assess the frequency of MGMT promoter methylation in soft tissue sarcoma to identify patients eligible for alkylating agent chemotherapy such as temozolomide.